Pituitary transcriptome analysis of mandarin fish (Siniperca chuatsi) reveals dietary 17α-methyltestosterone disturbs hypothalamic-pituitary-gonadal axis by FSH signaling pathway - Chong Han; Shiyan Liu; Kaichun Chen; Simin Zhong; Ming Li; Yanlin Jiang; Muzhi Yang; Yan Zhang; Mingjun Fan; Yong Zhang; Jin Zhang (Aquaculture Reports, 2024)
17α-methyltestosterone (MT), as a synthetic androgen, has been widely used in medicine and aquaculture industry. However, the related molecular regulating mechanism of MT effects on hypothalamic-pituitary-gonadal axis has not been well addressed. This study first evaluated the effects of MT treatment on pituitary of mandarin fish (Siniperca chuatsi). Transcriptome analysis revealed a lot of differentially expressed genes were found in pituitary after MT treatment in early stage (10 and 20 dat), with a relatively few genes found in late stage (30 and 40 dat). Among them, several reproduction related genes were significantly upregulated after MT treatment, while only the expression of follicle-stimulating hormone beta submit (fshb) was significantly inhibited in all stages. Moreover, in vitro experiment also revealed MT significantly inhibited the expression of fshb and promoted the expression of androgen receptors in pituitary. However, dual-luciferase assay revealed that MT activated the promotor activity of fshb via androgen receptors. Finally, we also demonstrated FSH could directly activate the promotor of cyp19a1a by several ways. In all, we first demonstrated exogenous MT could inhibit the expression of fshb in pituitary and further decrease the production of estrogen in gonad by FSH signaling pathway in mandarin fish.